THE ROLE OF PARAMILITARY FORMATIONS IN MODERN ARMED CONFLICTS: STATUS, DILEMMA AND CONTROVERSIES (Heritage, 2023)
Modern armed conflicts have made paramilitary formations a topical issue, which is thematized in international humanitarian law and national legislations. In addition to existing traditional notions of a mercenary and a foreign fighter, other notions have emerged in recent years, namely the notion of a foreign terrorist fighter and the concept of private military and security companies (PMSC). The aim of this paper is to point out the key problems related to their determination, that is, status, as well as dilemmas and controversies that arise in relation to their legal treatment, including their participation in modern armed conflicts. Based on a review of relevant literature, an analysis of documents, official announcements and media content, four categories of paramilitary formations were presented. As a framework for illustrating the perceived dilemmas and controversies the wars in Afghanistan, Iraq and Ukraine were used as examples.
Keywords: paramilitary formations, mercenaries, foreign fighters, foreign terrorist fighters, PMSC, modern armed conflicts